Studi Penciptaan Karya Seni Rupa Wayang Beber Menggunakan Teknik Kolase Dengan Memanfaatkan Koran Bekas - Zarkasi, Much. Sofwan (Institut Seni Indoensia Surakarta, 2011)
Research the creation of works of art that took the title of the Creation Studies Fine Art Wayang Beber Using Collage Techniques Used by Utilizing newspaper, in 2011 by Much. Sofwan Zarkasi aims to open up wide open opportunities related to creativity in the art tradition in an increasingly globalized environment and create works of art beber puppets using collage techniques using newsprint as an alternative form in viewing works of art beber puppet that had been used paint manufacturer with natural dyes and painting techniques. The basic idea of this research is that there are opportunities that exist related to creativity and experimentation in the tradition-dimensional work of art as the development of an increasingly globalized era, as well as the opportunity to present a stimulus and a new perspective related beber puppet who started rare existence. The creation of art works using puppets beber tekonik collage using old newspapers is an engineering development ever undertaken in the work of art is a collage using feathers (hair painting) and collages using decoration technique that has been there on the puppet beber is using decoration techniques which is a technique attached using glue and old newspapers that has been there and selected according to the color needs. The method is applied in the creation of the work on this research is a method of experimentation is the process of conducting experiments that put forward from design planning, preparation and realization of the work in the media. Keywords : arts, puppet, beber, paper, collages